Estimation of Laundry-derived Microfiber Discharges into Wastewater: A Case Study in Hanoi City - Thi Thanh Nga, Cao; Thi Oanh, Doan; Thi Phuong Quynh, Le; Thi My, Nguyen; Thi Thu Ha, Pham; Thi Hai Linh, Dang; Thi Thuy, Duong (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2SDO - 10.25073/2588-1094/vnuees.5419, 2025)
Household wastewater is a major source of microplastic (MP) emissions, with domestic laundry recognized as a key pathway for microfiber release into aquatic systems. Although previous studies have confirmed this emission pathway, data from Vietnam remain limited. This study aimed to provide preliminary data on microfiber release (including abundance, physical characteristics, and polymer composition) from household washing. Thirty laundry wastewater samples from Hanoi households were analyzed to assess microfiber abundance and characteristics. Microplastic abundance was very high, averaging 96,296 ± 68,938 microplastics/m³, with fibers comprising 99.6% of total MPs. Twelve polymer types were identified, with polypropylene (PP) being predominant (52.2%). Most fibers were 300-1,000 µm in length, and eight color groups were recorded, with black (39.18%) and white (26.07%) being the most common. These findings highlight that household laundry wastewater is a significant source of microfiber emissions, posing potential risks to both the environment and human health.